Does the fundamental transformation deter trade? An experiment - Christoph Engel; Eric Helland (Max Planck Institute for Research on Collective Goods, 2020)
Oliver Williamson has coined the term "fundamental transformation". It captures the following situation: before they strike a deal, buyer and seller are protected by competition. Yet thereafter they find themselves in a bilateral monopoly. With common knowledge of standard preferences, both sides conclude the contract regardless if its expected value exceeds their outside options. We run an experiment to test whether additional behavioral reasons deter mutually beneficial trade. If the risk materializes, another individual makes a windfall profit. She does so by intentionally exploiting the first individual. The first individual is let down, although she has knowingly exposed herself to this risk. Participants sell the opportunity to enter the contractual relationship at a price below its expected value. This effect is driven by risk aversion, and already present if the risk is stochastic. Behavioral effects are heterogeneous. About a quarter of participants exhibit the hypothesized additional deterrent effect.
Keywords: B21; C91; D22; D43; K12; L12; L14; 330; fundamental transformation; bilateral monopoly; sunk cost; Oliver Williamson; windfall profit; exploitation; let down aversion